DETECTION OF PIG DNA FRAGMENTS IN HALAL UNLABLED LIPSTICK SAMPLES USING CONVENTIONAL PCR - Misbakhul Munir; Siti Malihatus Sa'adah; Siti Latifa; Nabila Ayu; Oki Rahmatirta W; Najwa Maulidina P; Ameliora C E; Eko Prasetya; Yuanita Rachmawati (Universitas Negeri Medan, 2021)
From a Muslim perspective, it is very important to know the content, raw materials, and processing of the raw materials used in the cosmetic products used. One type of cosmetics that is most often used is lipstick. However, many lipsticks circulating in Indonesia are not equipped with a halal logo. One of the ingredients for lipstick is pork derivatives. These pig derivatives can be detected using PCR. Based on this background, this study aims to test the presence of pig DNA in lipstick samples that have not been certified halal on the market using 4 combinations of pig DNA fragments coding primers by using the conventional PCR method. Five commercial lipstick samples were selected by purposive sampling. DNA isolation was carried out according to the Wizard Promega Universal Kit. The PCR process was carried out with temperature optimization as follows: Predenaturation 98oC: 2 minutes, denaturation of 95oC: 30 seconds, Annealing 61oC: 30 seconds, Extension 72oC: 40 seconds, and Postextension 72oC: 3 minutes. The results showed that of the 5 samples tested by PCR using 5 kinds of primer combination, none of the samples were suspected to contain pork DNA. DNA isolation is the most difficult step in the lipstick sample detection process. Even though the detection result is negative, it is necessary to carry out further tests which become the Gold Standard of DNA-based testing using Real Time PCR.